Pengaruh Stres Kerja, Kecerdasan Emosional Dan Dukungan Rekan Kerja Terhadap Burnout Guru Di Sekolah SMP Negeri 1 Pematang Bandar Kabupaten Simalungun - Della Indriyani; Normansyah Normansyah (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to determine the simultaneous and partial effects of work stress, emotional intelligence, and coworker support on teacher burnout. The research employed a sample of 52 respondents. The data analysis technique used was multiple linear regression. The F-test results showed that Fcount (18.169) > Ftable (2.80), indicating that work stress, emotional intelligence, and coworker support simultaneously affect burnout. The t-test results demonstrated that work stress has a positive and significant effect on burnout because tcount (5.543) > ttable (2.00958), emotional intelligence has a negative and significant effect on burnout because tcount (-5.534) < -ttable (-2.00958), and coworker support has a negative and significant effect on burnout because tcount (-2.910) < -ttable (-2.00958). The coefficient of determination test (Adjusted R Square) showed a value of 0.502, indicating that the independent variables consisting of work stress, emotional intelligence, and coworker support were able to explain burnout by 50.2%, while the remaining 49.8% was explained by other variables not included in this study.